Breast Cancer and Dietary Fat Intake: A correlational study (Nepal Journal of Epidemiology, 2019)
Background: Breast cancer (BC) is reported to be the most common malignancies affecting women worldwide. There is a sharp increase in the BC incidence rate over the past three decades as previously low risk countries are moving towards high -calorie western diets. Few epidemiologic studies along with animal experiments have ascertained the role of dietary fat in developing BC. This study aimed to determine the correlation between per capita dietary fat consumption and incidence of BC.Methods: Three major data bases were used to conduct this correlational study. The data regarding consumption of fat and breast cancer incidence from 88 countries across five continents were extracted. The correlation coefficients between the incidence of BC and the fat consumption from the year 1990 to 2007 were calculated.Results: A statistically significant (P